The immunoglobulin domain of the sodium channel β3 subunit contains a surface‐localized disulfide bond that is required for homophilic binding. Issue 2 (1st November 2012) - Yereddi, Nikitha R.; Cusdin, Fiona S.; Namadurai, Sivakumar; Packman, Len C.; Monie, Tom P.; Slavny, Peter; Clare, Jeffrey J.; Powell, Andrew J.; Jackson, Antony P.
Abstract : The β subunits of voltage‐gated sodium (Nav ) channels possess an extracellular immunoglobulin (Ig) domain that is related to the L1 family of cell‐adhesion molecules (CAMs). Here we show that in HEK293 cells, secretion of the free Ig domain of the β3 subunit is reduced significantly when it is coexpressed with the full‐length β3 and β1 subunits but not with the β2 subunit. Using immunoprecipitation, we show that the β3 subunit can mediate trans homophilic‐binding via its Ig domain and that the β3‐Ig domain can associate heterophilically with the β1 subunit. Evolutionary tracing analysis and structural modeling identified a cluster of surface‐localized amino acids fully conserved between the Ig domains of all known β3 and β1 sequences. A notable feature of this conserved surface cluster is the presence of two adjacent cysteine residues that previously we have suggested may form a disulfide bond. We now confirm the presence of the disulfide bond in β3 using mass spectrometry, and we show that its integrity is essential for the association of the full‐length, membrane‐anchored β3 subunit with itself. However, selective reduction of this surface disulfide bond did not inhibit homophilic binding of the purified β3‐Ig domain in free solution. Hence, the disulfide bond itself is unlikely to be part of the homophilic binding site. Rather, we suggest that its integrity ensures the Ig domain of the membrane‐tethered β3 subunit adopts the correct orientation for productive association to occur in vivo. —Yereddi, N. R., Cusdin, F. S., Namadurai, S., Packman, L. C., Monie, T. P., Slavny, P., Clare, J. C., Powell, A. J., Jackson, A. P. The immunoglobulin domain of the sodium channel β3 subunit contains a surface‐localized disulfide bond that is required for homophilic binding. FASEB J. 27, 568–580 (2013). www.fasebj.org